Orphan crops and sustainability transitions in agri-food systems: Towards a multidimensional and multilevel transition framework - El Bilali, Hamid; Cardone, Gianluigi; Rokka, Susanna; De Falcis, Eleonora; Naino Dika, Abdel Kader; Diawara, Ali Badara; Nouhou, Bassirou; Ghione, Andrea (SCITE Explore, 2023)
Neglected and underutilized species (NUS i.e. orphan crops) are widely claimed to contribute to sustainable development. However, the relationship between NUS and sustainable agri-food systems is still unclear. Therefore, this paper analyses the role of NUS in the transition towards sustainable and resilient agri-food systems and identifies actions needed and levers of change. It draws upon a systematic review of 35 articles identified through a search performed in July 2022 on the Web of Science. The analysis of the literature was conducted following the Multi-Level Perspective on socio-technical transitions (MLP) and its three elements viz. niches, sociotechnical regime and sociotechnical landscape. The review suggests that the transition dynamics and success depend not only on the features of the niche NUS (cf. strengths and weaknesses), regime (cf. barriers to change and competitiveness of major crops with NUS) and landscape (cf. macro-trends and policies) but also on the interactions among them. The levers of change lie in the areas of policy, market and finance, technology, culture, and science and innovation. Further research is needed to elucidate the mechanisms leading to the mainstreaming of NUS into agri-food systems as well as the dynamics of interaction between niche NUS and commercial, staple crops.
Keywords: niche; NUS; orphan crops; sustainability transitions; sustainable agriculture; sustainable food systems